Efek Ekstrak Kulit Manggis (Garcinia Mangostana Linn) sebagai Anti Inflamasi pada Tikus Model Aterosklerotik - Salva Reverentia Yurista; Fathiyah Safithri; Djoni Djunaedi; Djanggan Sargowo (The Indonesian Heart Association, 2012)
Background. Atherosclerosis is an inflammatory disease characterized by intense immunological activity, which immune responses participate in every phase of atherosclerosis. On fundamental importance in atherogenesis is nuclear factor-?B(NF- ?B) that regulates activation of adhesion molecules (ICAM-1) and secretion of pro-inflammatory cytokines such as tumor necrosis factor(TNF-a) interleukin-1(IL-1), and interleukin-6(IL-6).Aims. The extract from pericarp of mangosteen (Garcinia mangostana Linn) were carried out to investigate for anti-inflammatory activity in rat models with atherosclerosis.Methods. The subjects of the study were 30 albino rats of (Rattus novergicus Strain wistar), divided into 5 groups with six rats in each group. Group I comprises normal healthy rats remains untreated for 90 days; Group II comprises of high cholesterol diet induced atherosclerotic rats for 90 days; Group III, IV, and V comprise of high cholesterol diet induced atherosclerosis and were administered extract from pericarp of mangosteen orally (200mg/kg; 400 mg/kg, 800 mg/kg) daily for 90 days. After 90 days treatment, rats were decapitated and blood was sample collected from the aorta for determination level of TNF-aand IL-1 by ELISA. Aorta was taken to observe the expression of NF-kB, ICAM-1, and IL-6 using immunohistochemical techniques.Results. Oral administration (800 mg/kg) of the extract from pericarp of mangosteen significantly decreased the level of TNF-a, and IL-1 and also reduced the expression of NF-kB, ICAM-1, and IL-6.Conclusion. These results suggest that the extract from pericarp of mangosteen (Garcinia mangostana Linn)possess anti-inflammatory actions by reducing level of TNF-a, IL-1, and also reduce the expression of NF-kB, ICAM-1, and IL-6 that prevent the development of atherosclerosis.